Vegetative propagation of mulberry (Morus, nigra L) for greening of roads (Eurasian Research Bulletin, 2024)
Special attention was paid to the identification of highly scenic, promising, plant species resistant to various external harmful factors and the development of efficient and optimal methods of rapid reproduction as the priority directions of greening of highways in the world. In this regard, new varieties and forms of decorative species were created, the possibilities of trees and shrubs in modern landscaping were evaluated, and new methods of vegetative propagation were created.